Decision Making Analysis In The Implementation Of Campus-Based Thematic Banking Cafe Using The Analytical Hierarchy Process (AHP) Approach – Case Study: Thematic Model Banking Café Bni Trisakti Kampus A Sub-Branch - Pinandhita, Ifan; Siallagan, Manahan (International Journal of Social Service and Research, 2025)
In the pursuit of innovative and practical learning environments, the concept of a campus-based thematic banking café has emerged as a promising initiative that integrates education, entrepreneurship, and financial literacy. This research analyzes the decision-making process behind the implementation of such a café using the Analytical Hierarchy Process (AHP) methodology. The aim is to identify and prioritize key factors that influence the feasibility and success of the initiative within a university setting. A hierarchical decision model was developed, incorporating five main criteria: educational impact, financial feasibility, operational sustainability, stakeholder support, and technological integration. Through pairwise comparisons and expert input from university stakeholders, including academic staff, students, financial managers, and banking partners, priority weights were calculated for each criterion using AHP. The results show that educational impact is the most critical factor, emphasizing the role of the café in supporting academic goals and experiential learning. Financial feasibility and operational sustainability also received significant attention, while technological integration and stakeholder support were found to be important but secondary considerations. The findings demonstrate that AHP is an effective tool for multi-criteria decision-making in higher education contexts. It enables universities to align diverse perspectives and justify strategic decisions through a structured and transparent framework. This study offers a practical reference for educational institutions considering similar campus-based initiatives and highlights the potential for cross-sector partnerships to enhance student learning experiences.